Rickets Due to Distal Renal Tubular Acidosis– an Uncommon Presentation of Wilson’s Disease - Azad, Md Abul Kalam; Alam, Afroja; Quayum, Shaheen Lipika; Anwar, AFM Azim; Anjum, Monjila (Bangladesh Journal of Medicine, 2018)
Rickets is a disease of bone mineralization of growth plate. Refractory rickets can be caused by distal (type 1) renal tubular acidosis (RTA). A number of conditions can result in distal RTA and Wilson’s disease is an uncommon entity. Wilson’s disease is a rare autosomal recessive disorder of copper metabolism with diverse presentations. We describe a case of refractory rickets due to distal RTA, caused by Wilson’s disease. Diagnosis of Wilson’s disease was confirmed with presence of Kayser–Fleischer (K–F) rings and high urinary copper. Further investigations revealed urinary acidification defect with hypercalciuria pointing towards distal RTA. He was treated with penicillamine & oral Zinc and significant clinical improvement was observed. Bangladesh J Medicine Jul 2018; 29(2) : 84-86